Students' Writing through Project-based Learning at EFL Classroom - Saiful Latif; Abdulhalim Daud (Jurnal Langua, 2023)
This study was intended to explore how the implementation of project-based learning in EFL classrooms and to find out how students' perspectives on the implementation of the project-based learning Model. The subject of the study was a class, consisting of 45 students of the English Education Study Program at one university in North Maluku, who was studying paragraph writing. The qualitative method is used to understand, explain, and interpret data. Observation and interviews were used in collecting multiple data, namely documentation and interview data. The data analysis used content analysis. The result of this study indicates that the use of Project Based Learning can help students to develop their writing paragraph abilities. It can be observed from the students in determining the topic sentence and using references, provided examples, and facts in writing the paragraph. Further, in the concluding sentence, students conclude their elaboration of the entire paragraph from both the topic sentence and supporting sentences. In addition, it is noted that good perceptions of the implementation of the Project Based Learning model in learning paragraph writing are shown by students.